T1 Mapping for Myocardial Fibrosis by Cardiac Magnetic Resonance Relaxometry—A Comprehensive Technical Review - Hamilton-Craig, Christian R.; Strudwick, Mark W.; Galloway, Graham J. (Frontiers in Cardiovascular Medicine, 2017)
CMR imaging has been widely used to assess myocardial perfusion and scar, and is the noninvasive gold standard for identification of focal myocardial fibrosis. However the LGE technique is limited in its accuracy for absolute quantification and assessment of diffuse myocardial fibrosis by technical and pathophysiological features. CMR Relaxometry, incorporating T1 mapping, has emerged as an accurate, reproducible, highly sensitive and quantitative technique for the assessment of diffuse myocardial fibrosis in a number of disease states. We comprehensively review detailed physics and development behind CMR relaxometry, the evidence base, and the clinical applications of this emerging technique.